The EU, migration and the politics of administrative detention - Ceccorulli, Michela; Labanca, Nicola (Routledge advances in European politics, 2014)
"Migration is now regarded as a security issue, both in public debate and government policies. In turn, the phenomenon of detention as a governance practice has emerged, and the developing presence of camps in Europe for migrants has given rise to a tangle of new and complex issues.This book examines the phenomenon of irregular immigration, and provides a comprehensive picture of the practices and the implications of detention of migrants within and on the borders of the European Union. It analyses 'detention' as a tool of governance and in doing so explores several key themes: The security threat for Europe. The security governance processes enacted to handle irregular immigration. The forms of detention in different geographical contexts. The effectiveness of the EU's approach to the issue. The EU, Migration and the Politics of Administrative Detention will be of interest to students and scholars of the EU's external relations, migration, human rights, European politics and security studies"--